Pengembangan Media Pembelajaran Tipografi berbasis Website pada Materi Kingdom Plantae - Arham, Arham; Maulana, Andi; Syahriani, Syahriani (Al Asma: Journal of Islamic Education, 2025)
Biology learning in schools still uses conventional media such as textbooks and PowerPoint, which are less interesting for students. Abstract and dense materials, such as Kingdom Plantae, are often difficult to understand, thus inhibiting the effectiveness of learning. This condition indicates the need for the development of more innovative learning media that are in accordance with technological developments to help students understand the material more optimally. This study aims to develop website-based typography learning media on Kingdom Plantae material for grade X students that are valid, practical, and effective. This study is a research and development (Research and Development) using the ADDIE model, which consists of five stages, namely: Analysis, Design, Developmen, Implementation, and Evaluation. The product developed is a website-based typography learning media. To test the quality of the product, three stages of testing were carried out, namely validity testing by material and media experts, practicality testing by teachers and students, and effectiveness testing through student learning outcomes. The subjects of the trial in this study were 20 grade X students. The results of the study indicate that the website-based typography learning media developed by the media meets the criteria for being suitable for use in the learning process because it meets the criteria of being valid, practical, and effective. The implications of this study indicate that website-based typography learning media can be an innovative alternative that supports more interactive biology learning, makes it easier for teachers to deliver materials, and encourages students' learning independence.